Exploring The Concept of Geometry in Halasuji Kanre Ana’: Synergy of Mathematics with Local Culture - Sri Satriani; Kristiawati; Muhammad Rizal Usman; Ranti Kurniasih (Journal of Local Wisdom in Education, 2025)
This study addresses the persistent challenge of teaching geometry as an abstract and culturally detached subject by exploring the integration of local wisdom through an ethnomathematical perspective. The study examines halasuji kanre ana’, a traditional Bugis–Makassar bamboo artifact used in wedding rituals, as a contextual learning resource. The urgency of this research lies in the limited utilization of three-dimensional cultural artifacts in formal geometry instruction. The objective of the study is to identify and analyze the geometric concepts embedded in halasuji kanre ana’ and to evaluate its potential contribution to culturally contextual geometry learning. Employing a qualitative ethnomathematical approach, data were collected through artifact observation, documentation, and analysis of construction patterns and weaving structures, and were interpreted using thematic and conceptual analysis. The results reveal that halasuji kanre ana’ embodies a wide range of geometric concepts, including solid geometry, plane figures, line and angle relationships, tessellation, symmetry, and geometric transformations. These concepts are systematically interconnected within both the artifact’s structural framework and its decorative pattern. The novelty of this study lies in its comprehensive examination of a three-dimensional ritual artifact that integrates multiple geometric domains within a single cultural object, moving beyond the predominantly two-dimensional focus of prior ethnomathematics research. The study concludes that halasuji kanre ana’ has strong potential as a culturally contextual learning medium that bridges abstract mathematical concepts with students’ cultural experiences. This research contributes to the field of local wisdom education by providing a theoretically grounded framework for integrating indigenous cultural artifacts into mathematics instruction, thereby supporting meaningful learning, cultural preservation, and the development of inclusive and contextually relevant educational practices.